Review of non‐invasive vulvovaginal rejuvenation. (5th December 2019) - Photiou, L.; Lin, M.J.; Dubin, D.P.; Lenskaya, V.; Khorasani, H.
Abstract: Vulvovaginal atrophy (VVA) or genitourinary syndrome of menopause (GSM) may affect up to 90% of menopausal women. Features include vulvovaginal atrophy, vulvovaginal laxity, vulvovaginal dryness and irritation, dyspareunia, anorgasmia and urinary symptoms. The vulva, vagina and bladder are oestrogen‐responsive tissues, but oestrogen replacement therapy is not possible in women who have hormone‐responsive cancers or normal oestrogen levels. Therefore, there is a role for alternative treatments. To date, three non‐surgical energy‐based therapies have been proposed: fractional microablative CO2 laser, erbium:YAG laser and temperature‐controlled radiofrequency (RF). Our objective was to assess the available evidence for the safety and efficacy of erbium:YAG laser, microablative fractional CO2 laser and RF in the treatment of VVA/GSM. The authors reviewed the current published literature evaluating these therapies. All three therapies appear safe; however, all the studies were uncontrolled and used different protocols and outcome measurements. Therefore, comparison of treatments is difficult. It appears that there is more evidence in favour of the CO2 laser than the erbium:YAG laser. Both lasers have more evidence than RF. In conclusion, microablative CO2 laser, erbium:YAG laser and RF may be offered to patients suffering from VVA/GSM as an alternative or adjunct to conventional therapies. Further well‐conducted controlled studies are needed.